1988
DOI: 10.1080/14640748808402296
|View full text |Cite
|
Sign up to set email alerts
|

The Topology of Performance Curves during 72 Hours of Sleep Loss: A Memory and Search Task

Abstract: Three levels of working memory load of a visual search (Memory and Search) task were tested in a 72-hour sleep deprivation paradigm. General performance and accuracy decrease over time with monotonic and rhythmic components. The signal detection discriminability index, d', decreases monotonically with rhythmic variations. The index of response bias, β, shows no monotonic trend, but significant circadian rhythmicity. The extent of the monotonic and rhythmic changes in accuracy and in d’ is directly related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 23 publications
0
44
2
Order By: Relevance
“…However, when data collection was continued into the night, it soon became apparent that overall performance on this short-term memory task in fact paralleled the body temperature cycle. These data are consistent with the results of a recent 72-h sleep deprivation study conducted by Babkoff et al (1988). Contrary to the earlier claims noted above, they found that performance on a Memory and Search task reached a trough between 02.00 hours and 06.00 hours using a 2-, 4-, or 6-letter target.…”
Section: Discussioncontrasting
confidence: 53%
“…However, when data collection was continued into the night, it soon became apparent that overall performance on this short-term memory task in fact paralleled the body temperature cycle. These data are consistent with the results of a recent 72-h sleep deprivation study conducted by Babkoff et al (1988). Contrary to the earlier claims noted above, they found that performance on a Memory and Search task reached a trough between 02.00 hours and 06.00 hours using a 2-, 4-, or 6-letter target.…”
Section: Discussioncontrasting
confidence: 53%
“…the more usual sequence is for seven 12 h night shifts to be followed immeDownloaded by [Columbia University] at 21:11 05 February 2015 diately by seven 12 h day shifts. Thus, when changing shifts at the end of the first week, operators have little or no sleep over a 24 h period with potentially adverse effects on sleepiness, negative mood, and cognitive task performance (Babkoff et al 1988. Englund er al.…”
Section: Shift Duration and Shifi Rotation Patternsmentioning
confidence: 97%
“…However, the exact benefits of recovery sleep of various lengths are not fully known, and existing studies do not provide consistent results. Both Babkoff et al (1988) and Haslam (1982) reported that 4 h of sleep lead to partial recovery of performance after 73 and 90 h of TSD, respectively. On the other hand, Ryman et al (1985) reported that 3 h of sleep after only 17 h of continuous work did not improve performance.…”
Section: Introductionmentioning
confidence: 99%